James Thomas Ward papers - Ward, James Thomas, 1820-1897.
Sixty-two bound volumes of diaries, writings, notes, family and autobiographical material, clippings, and pamphlets featuring Ward's life and work as a circuit minister of the Methodist Protestant Church in Maryland and West Virginia, as pastor of the First Methodist Protestant Church (Philadelphia, Pa.), president of Western Maryland College (Westminster, Md.), and president of Westminster Seminary (Westminster, Md.). The diaries include personal reflections and observations.
Clergyman, author, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ward family; First Methodist Protestant Church (Philadelphia, Pa.); Methodist Protestant Church (U.S. : 1830-1939); Western Maryland College; Westminster Theological Seminary (Westminster, Md.); Circuit riders -- Maryland; Circuit riders -- West Virginia; Methodist Church -- Maryland; Methodist Church -- Pennsylvania -- Philadelphia; Methodist Church -- West Virginia; Authors; Clergy; Educators